The well-being of working couples: A sociological study grounded Islamic values - Amer Hudhaifah Hamzah; Zaifuddin Md Rasip; Habibah@Artini Ramlie; Muhamad Suhaimi Taat; Sakeena Zahidah Mohamed Shah Redza (RSIS International, 2025)
This study examines the well-being of working couples in the Klang Valley by focusing on the clarity, involvement, and balance of dual roles, as well as their relationship with household well-being. Employing a mixed-method approach in two phases, the first phase involved an online questionnaire (N = 119), while the second comprised interviews and focus group discussions. Findings indicate that dual-role involvement and work-family balance are significantly correlated with well-being, whereas role clarity alone is insufficient. Five core components were identified—belief, moral values, communication, relational strength, and management— organized into two skill dimensions: intrapersonal and managerial. An initial review of Islamic values underscores the importance of applying knowledge through practice and achieving internal-external balance as normative guidance aligned with the natural order (sunnat al-kawn). Islamic teachings emphasise that knowledge must be accompanied by action, and that inner transformation is the foundation of outward well-being. The strength of the heart and intrapersonal values such as faith, sincerity, and responsibility serve as key determinants of marital harmony. The study also highlights that household well-being is rooted in the integrity of internal values, which subsequently shape communication, relationships, and shared life management. This study offers both empirical and spiritual foundations for the development of holistic family well-being policies, although it is limited by sample imbalances in terms of gender, socioeconomic status, and education level.